SURFACE-CHEMISTRY OF SODIUM, CHLORINE, AND OXYGEN ON CHROMIUM AND CHROMIUM(III) OXIDE - Foord, J; Lambert, R (1986)
Chemisorption and coadsorption of sodium, chlorine, and oxygen on Cr(100) and on epitaxially grown Cr2O3(0001) surfaces have been studied by LEED, AES, TDS, and Δφ techniques. Na adsorption on Cr(100) results in the formation of positively charged, ordered monolayers, exhibiting strong lateral repuisions and a heat of adsorption of 175 kJ mol-1 at low coverages; subsequent exposure to oxygen brings about oxidation of the Na phase and the underlying Cr(100) lattice. Coadsorption of Na and Cl on Cr(100) causes island formation of (100)-oriented NaCl and implies an appreciable lateral mobility for the surface species at 300 K; at high chlorine coverages evidence is presented suggesting formation of CrCl2 and a mixed CrNaxCl2+x corrosion phase. Na adsorption on outgassed Cr2O3 exhibits characteristics similar to the interaction of alkalis with transition metals, although the Na is more strongly bound than on Cr(100). When heated in the presence of oxygen, reaction of adsorbed Na with the underlying Cr2O3 lattice takes place, resulting in formation of a mixed Na-Cr-O compound. Chlorine adsorption on the outgassed Cr2O3 surface results in the appearance of two TDS states, chlorine being evolved at low temperatures and chromium chloride(s) desorbing at high temperatures. This latter process is suppressed by coadsorbed oxygen and the nature of the reactions occurring is discussed. Electron-stimulated desorption of chlorine is observed in the Cr(100)/Na/Cl and Cr2O3(0001)/Cl chemisorption systems and cross sections for the stimulated desorption processes are presented. © 1986 American Chemical Society.